MANAJEMEN KLINIS CU-SIL DENTURE PADA PASIEN DENGAN SEDIKIT GIGI ASLI YANG TERSISA - Silmi Gusdayuni; Eni Rahmi (Faculty of Dentistry Universitas Andalas, 2018)
Nowadays one of the prime concern in dentistry is on preservation of remaining natural teeth. Many patients require replacement of missing teeth and associated structures to enhance appearance, improve masticatory efficiency, prevent unwanted movement of teeth (overeruption/ drifting), and/ or improve phonetics. Presence of few teeth in oral cavity helps in preserving alveolar ridge integrity, maintain the proprioception, and gives psychological benefit to the patient. This case report presents a case of a 54-years-old female with few remaining teeth, one remaining tooth in maxilla and two remaining teeth in mandible. Patient wants to get her masticatory function and aestethic back with maintain her remaining teeth. Cu-sil denture is one of the simplest removable partial denture that can replace missing teeth where only few teeth remain in oral cavity. A Cu-sil denture is a denture with holes, lined by a gasket, the holes that providing space for remaining natural teeth to emerge into the oral cavity through the denture.